Integrasi Teknologi dan Media ke dalam Pembelajaran Abad 21 - Masnita, Delmi; Syakban, Ismail; Nurhamidar, Nurhamidar; Sukmayeti, Sukmayeti; Wahyuni, Yessi (Lembaga Yasin AlSys, 2026)
Twenty-first-century learning requires mastery of critical thinking, creativity, collaboration, and communication skills that are aligned with technological developments and global demands, making the integration of technology and media a strategic component in improving the quality of instruction. This study aimed to examine the integration of technology and media in twenty-first-century learning and its implications for enhancing the quality of learning processes and outcomes. A qualitative approach was employed using a library research method through the analysis of various relevant journal articles, reference books, and educational policy documents. The findings show that the integration of technology and media plays a crucial role in creating interactive, effective, and learner-centered instruction, while simultaneously supporting the development of digital literacy and increasing students’ motivation and engagement in learning. On the other hand, the implementation of technology and media integration still faces several challenges, particularly related to teacher readiness, levels of digital literacy, and disparities in access to technological facilities. Therefore, the integration of technology and media requires careful planning, the enhancement of teachers’ competencies, and adequate infrastructure support so that it can be optimally implemented and genuinely sustain the realization of high-quality, inclusive, and contextually relevant twenty-first-century learning.